Transformation of the Chinese party-state at prefecture and county level - Hairong Lai; Maria Csanadi (Hungarian Academy of Sciences, Institute of Economics, 2003)
The study describes the acceleration of the disintegration and withdrawal of the party-state network and transformation of the system on national level, and empirically surveys the impact of the hardening reproduction constraints of the party-state network since 1994 in three Chinese prefectures and six counties. We track the reactions to the hardening reproduction constraints at these levels and the consequences of these reactions on the transformation of the party-state network at those levels. We make an effort to demonstrate the differences in impact, reactions and consequences among the given administrative levels and between them. We also try to detect how does this process change the relationship among the actors within the net (party-state and economic decision-makers) and between those within and outside the net. The survey is based on the implementation of the Interactive Party-State model (Csanádi, 1997, 2003) that serves as a device and approach for comparative empirical analysis. The surveyed prefectures and counties provided a test-field for the postulates of the model. More than 70 interviews with provincial, prefecture and county level party- and state officials, different level statistics, national and local level documents and secondary sources forged the raw material for the study.
Keywords: 330